Functional capacity and mental state of patients undergoing cardiac surgery - Bruna Corrêa; Dannuey Machado Cardoso
Abstract Introduction: Cardiovascular diseases are a serious public health problem in Brazil. Myocardial revascularization surgery (MRS) as well as cardiac valve replacement and repair are procedures indicated to treat them. Thus, extracorporeal circulation (ECC) is still widely used in these surgeries, in which patients with long ECC times may have greater neurological deficits. Neurological damage resulting from MRS can have devastating consequences such as loss of independence and worsening of quality of life. Objective: To assess the effect of cardiac surgery on a patient's mental state and functional capacity in both the pre- and postoperative periods. Methods: We conducted a cross-sectional study with convenience sampling of subjects undergoing MRS and valve replacement. Participants were administered the Mini-Mental State Exam (MMSE) and the Duke Activity Status Index (DASI) in the pre- and postoperative periods, as well as before their hospital discharge. Results: This study assessed nine patients (eight males) aged 62.4 ± 6.3 years with a BMI of 29.5 ± 2.3 kg/m2. There was a significant decrease in DASI scores and VO2 from preoperative to postoperative status (p = 0.003 and p = 0.003, respectively). Conclusion: This study revealed a loss of cognitive and exercise capacity after cardiac surgery. A larger sample however is needed to consolidate these findings.